Magnetic susceptibility as an indicator of heavy metal traffic pollution - KLUČIAROVÁ, Denisa; GREGOROVÁ, Dagmar (Contributions to Geophysics and Geodesy, 2008)
Heavy traffic presents a problem with pollution not only of the air, but also of soils around the frequently used roads. In this case, significant pollutants are heavy metals – mostly lead, iron, chrome, nickel and their compounds. In the Malé Karpaty Mts. we picked a stretch of the mountain road experiencing heavy traffic for testing the magnetic mapping – the progressive proxy method of detecting the heavy metal pollution in the surrounding soil. The total number of 96 topsoil samples were collected along the road, and investigated for the mass specific magnetic susceptibility. The results show that this physical parameter is significantly increased in the topsoil close to the road. These elements and their compounds are often altogether bound on the humid soil constituents; therefore higher values of magnetic susceptibility and their decrease with distance from the road displace positive correlation not only with ferrimagnetic, but also of the affined paramagnetic components. The measurement of magnetic susceptibility of soils can be, in this case, used as a supplemental method to the geochemical mapping; method, which allows to assess, in a simple, cheap and rapid way the level of soil pollution at sites, where the geochemical data are missing.